MODELO DE PREDIÇÃO PARA O MERCADO ACIONÁRIO BASEADO NA LÓGICA FUZZY - Almeida, Allisson Jorge Silva (2015)
This work aims to present a prediction model for the stock market based on fuzzy logic that contributes to the negotiators of this order in the simulation of operations prior to before their implementation. To achieve this purpose, we used historical data of São Paulo Stock Exchange to perform the mathematical calculations needed regarding the technical indicators used, RSI - Relative Strength Index, MACD - Moving Average Convergence Divergence and the Beta Index. The following data were transformed into linguistic fuzzy variables yielding the data set to be applied to Fuzzy Control System. Two real assets were used in companies, and PETR4 VALE5 for the simulations. The results showed that the model provides results consistent with the changes in the current market. Thus, it can be used as a support tool in decision making in the stock market.